Numerical Analysis of Nonstationary Thermistor Problem (Journal of Computational Mathematics, 1994)
The thermistor problem is coupled system of nonlinear PDEs which consists of the heat equation with the Joule heating as a source, and the current conservation equation with temperature dependent electrical conductivity. In this paper we make a numerical analysis of the nonsteady thermistor problem. $L^∞(Ω), W^{1,∞}(Ω)$ stability and error bounds for a piecewise linear finite element approximation are given.